Teachers’ engagement with published research: addressing the knowledge problema - Cain, Tim (The Curriculum Journal, 2015)
Despite the increased interest in research impact, there is very little empirical evidence that educational research can inform practice directly, and furthermore, a body of literature which suggests that this is, in principle, impossible. This paper reports on a study in which secondary school teachers were given research findings about teaching gifted and talented students, and were supported, over a 12-month period, to incorporate findings into action research projects of their own devising. A theoretical framework from the research literature was used to investigate the process by which knowledge generated from research, was transformed into teachers’ pedagogical knowledge, thereby influencing the curriculum, pedagogy and provision for these students. Evidence suggests that teachers transformed propositional knowledge into practical knowledge by developing their conceptual understandings; they transformed abstract, impersonal knowledge into context-specific, personal knowledge by using cases from their previous experiences, and they transformed narrowly focused knowledge into broadly focused knowledge by imaginatively diffusing it into areas beyond those in the original research. Implications for research and practice are discussed.